The causes of stillbirths in south Asia: results from a prospective study in India and Pakistan (PURPOSe) - Elizabeth M McClure, PhD; Sarah Saleem, MBBS; Shivaprasad S Goudar, MD; Shiyam Sunder Tikmani, MBBS; Sangappa M Dhaded, MD; Kay Hwang, BS; Gowdar Guruprasad, MD; Dhananjaya Shobha, MD; B Sarvamangala, MD; S Yogeshkumar, MD; Manjunath S Somannavar, MD; Sana Roujani, MBBS; et al. (Elsevier, 2022)
Summary: Background: South Asia contributes more than a third of all global stillbirths, yet the causes remain largely unstudied in this region. New investigations, including novel assessments of placental and fetal tissues, facilitate more precise determination of the underlying causes of stillbirth. We sought to assess underlying and contributing causes of stillbirth from settings in India and Pakistan. Methods: In this prospective cohort study (PURPOSe), we report the cause of death in stillbirths in hospitals in central India and south Pakistan (Davangere, India [three public and private hospitals] and Karachi, Pakistan [one public maternity and one children's hospital]). Women aged 15 years or older and with a known stillbirth (defined as a pregnancy at 20 or more weeks of gestation with the in-utero death of a fetus) weighing 1000 g or more were included in the study. Maternal clinical factors, placental evaluation, fetal tissue evaluation (from minimally invasive tissue sampling), and PCR for microbial pathogens were used to identify the causes of death. An expert panel reviewed available data for all stillbirths to identify the primary and contributing maternal, placental, and fetal causes of stillbirth. Findings: Between Sept 1, 2018, and Feb 12, 2020, 981 stillborns were included and, of those, 611 were reviewed by the expert panel. The primary maternal causes of stillbirth were hypertensive disease in 221 (36%) of 611 stillbirths, followed by severe anaemia in 66 (11%) stillbirths. The primary placental causes were maternal and fetal vascular malperfusion, in 289 (47%) stillbirths. The primary fetal cause of stillbirth was intrauterine hypoxia, in 437 (72%) stillbirths. We assessed the overlap of main causes and 116 (19%) stillbirths had intrauterine hypoxia, placental malperfusion, and eclampsia or pre-eclampsia indicated as primary causes of death. Infection (including of the placenta, its membranes, and in the fetus) and congenital anomalies also were causative of stillbirth. Interpretation: In south Asia, fetal asphyxia is the major cause of stillbirth. Several placental lesions, especially those associated with maternal and fetal vascular malperfusion and placental abruption, have an important role in asphyxia and fetal death. Maternal hypertension, and especially pre-eclampsia, is often the primary maternal condition associated with this pathway. Funding: Bill & Melinda Gates Foundation.